Socio-economic status of buffalo farmers and the management practices of buffaloes in selected areas of Bagerhat District of Bangladesh (Bangladesh Journal of Animal Science, 2013)
The study was conducted to investigate the socio-economic status of the buffalo farmers and the management practices of buffaloes at different villages of Boraikhali, Hoglabunia and Khawlia union of Morrelgonj upazilla in Bagerhat district of Bangladesh. A total of 60 respondents (20 from each union) were randomly selected from three unions. The data was collected through personal interviewing with pre-tested questioner. The investigation revealed that buffalo rearing was practiced by the middle (30-40 years) and old (>40 years) aged farmers than the young (